Financial exchange rates and international currency exposures - Philip R. Lane; Jay C. Shambaugh (Deutsche Bundesbank, 2008)
Our goal in this project is to gain a better empirical understanding of the international financial implications of currency movements. To this end, we construct a database of international currency exposures for a large panel of countries over 1990-2004. We show that trade-weighted exchange rate indices are insufficient to understand the financial impact of currency movements. We show that our currency measure has high explanatory power for the valuation term in net foreign asset dynamics: exchange rate valuation shocks are sizable, not quickly reversed and may entail substantial wealth redistributions. Further, we demonstrate that many developing countries hold short foreign-currency positions, leaving them open to negative valuation effects when the domestic currency depreciates. However, we also show that many of these countries have substantially reduced their foreign currency exposure over the last decade.
Keywords: F31; F32; 330; Financial integration; capital flows; external assets and liabilities; Devisenmarkt; Devisenhandel; Währungsreserven; Wechselkurspolitik; Welt